Review paper Skin changes in the course of inflammatory bowel disease - Kopeć, Karolina; Jankowska-Konsur, Alina; Maj, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Crohn’s disease and ulcerative colitis are classified as chronic inflammatory bowel diseases (IBD), which not only affect the intestinal tract but also involve other organs, including skin and mucous membranes. More than half of patients with IBD suffer from parenteral symptoms. Skin lesions may be related to the underlying disease and its complications or may have a reactive character. Most common dermatoses coexisting with inflammatory bowel diseases are: pyoderma gangrenosum, erythema nodosum, Sweet’s syndrome, polyarteritis nodosa, leukocytoclastic vasculitis, erythema multiforme, mucosal lesions and local complications (fistulae, fissures and abscesses). This paper presents a rich spectrum of dermatological conditions associated with IBD.